2019
DOI: 10.7717/peerj.6600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a toxoid fusion protein vaccine produced in plants to protect poultry against necrotic enteritis

Abstract: Background Necrotic enteritis (NE) is caused by type A strains of the bacterium Clostridium perfringens. Total global economic losses to the poultry industry due to NE is estimated to be over two billion dollars annually. Traditionally, NE has been effectively controlled by inclusion of antibiotics in the diet of poultry. However, recent concerns regarding the impact of this practice on increasing antibiotic resistance in human pathogens have led us to consider alternative approaches, such as vaccination, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Our previous data proved that the operon fusion of nontoxic antigens PlcC and GST-NetB delivered by Salmonella induce protection ( Jiang et al, 2015 ; Wilde et al, 2019 ). The effectiveness of the fusion of PlcC and NetB has also been demonstrate by other researchers ( Hunter et al, 2019 ; Katalani et al, 2020 ). Salmonella delivering fructose-1,6-bisphosphate aldolase, has also been proved to induce protection against C. perfringens challenge ( Wilde et al, 2019 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our previous data proved that the operon fusion of nontoxic antigens PlcC and GST-NetB delivered by Salmonella induce protection ( Jiang et al, 2015 ; Wilde et al, 2019 ). The effectiveness of the fusion of PlcC and NetB has also been demonstrate by other researchers ( Hunter et al, 2019 ; Katalani et al, 2020 ). Salmonella delivering fructose-1,6-bisphosphate aldolase, has also been proved to induce protection against C. perfringens challenge ( Wilde et al, 2019 ).…”
Section: Discussionsupporting
confidence: 67%
“…Vaccination with NetB as toxoid, detoxified subunit, or chimeric protein, could provide protection from the development of NE in chickens ( Mot et al, 2014 ; Rood et al, 2016 ). It has been delivered by Salmonella , plant, non-virulent C. perfringens strain or in nanoparticles ( Jiang et al, 2015 ; Lillehoj et al, 2017 ; Mishra and Smyth, 2017 ; Hunter et al, 2019 ; Wilde et al, 2019 ; Hoseini et al, 2021 ; Mauri et al, 2021 ). We previously showed that a regulated delayed lysis strain χ11802 delivering a plasmid pYA5112 encoding an operon fusion of PlcC and GST-NetB could induce partial protection against C. perfringens challenge immunized with a 2-dose regime in which chickens were immunized at 3- and 17-d of age ( Jiang et al, 2015 ; Wilde et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that the major antigen recognized by this immune response was a nonproteinaceous antigen suggests that although vaccines targeting C. perfringens toxins may reduce the risk or severity of disease, these and other vaccines targeting protein antigens are unlikely to induce killing or clearing of C. perfringens cells from the intestinal tract. This may explain why several toxoid vaccines and one pilin-based vaccine show reduction in C. perfringens-induced lesion scores in chickens but are unable to fully eliminate lesions in at least half of vaccinated birds (30,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Of great importance among plant expression systems, is the bean yellow dwarf geminivirus (BeYDV) system wherein the target gene of interest replicates highly efficiently within the plant cell nucleus [ 268 , 269 ]. The geminivirus system considerably shortens the product recovery time and generates high yields of the desired antigen or antibody [ 270 , 271 ]. Further, a single given vector based on the BeYDV system can express several multimeric proteins in a non-competing manner whereas RNA virus-based systems require the use of multiple viruses that are non-competing to generate different proteins [ 269 ].…”
Section: Plant-based Therapeutic Antibodiesmentioning
confidence: 99%